Hypopigmented pityriasis versicolor. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Pityriasis versicolor (PV) is a superficial mycosis caused more frequently by Malassetia globosa, favored by hormone-dependent sebum, genetic factors and hot-humid climate (1). In prepubertal children PV mainly affects the face (Fig. 3), whereas after puberty PV affects the upper trunk as in adults (Fig. 1). The most frequent color of PV lesions is white -hypopigmented PV (HyPV)-.